2021
DOI: 10.20892/j.issn.2095-3941.2021.0267
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell trajectories of melanoma cell resistance to targeted treatment

Abstract: Objective: Cellular heterogeneity is regarded as a major factor affecting treatment response and resistance in malignant melanoma. Recent developments in single-cell sequencing technology have provided deeper insights into these mechanisms. Methods: Here, we analyzed a BRAF V600E -mutant melanoma cell line by single-cell RNA-seq under various conditions: cells sensitive to BRAF inhibition with BRAF inhibitor vemurafenib and cells resistant to BRAF inhibition with vemurafenib alone or vemurafenib in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…As for lymphomas, also the transcriptional states along the GC reaction form a continuum on cellular resolution rather than a set of well-separated single cell states [ 46 ]. Notably, SOM-landscapes in general are able to recapitulate time-dependent trajectories along such a continuum in gene state space [ 66 ] as was shown for a wide spectrum of time-scales ranging from cell and tissue development [ 67 ] to evolutionary processes [ 68 , 69 ] using transcriptomic and genetic features.…”
Section: Discussionmentioning
confidence: 99%
“…As for lymphomas, also the transcriptional states along the GC reaction form a continuum on cellular resolution rather than a set of well-separated single cell states [ 46 ]. Notably, SOM-landscapes in general are able to recapitulate time-dependent trajectories along such a continuum in gene state space [ 66 ] as was shown for a wide spectrum of time-scales ranging from cell and tissue development [ 67 ] to evolutionary processes [ 68 , 69 ] using transcriptomic and genetic features.…”
Section: Discussionmentioning
confidence: 99%
“…For example, scRNA-seq of BRAF-mutant melanoma cells treated with the BRAF inhibitor vemurafenib, alone or in combination with MEK inhibitor cobimetinib or trametinib, showed seven separate cell clusters representative of distinct transcriptional states. Each treatment group showed enrichment of particular transcriptional states, 52 suggesting that the frequencies of these states change with treatment, and this dynamic change contributes to the overall heterogeneity. Similarly, in NRAS-mutant melanoma cells treated with combination MEK and CDK4/6 inhibitors, scRNA-seq revealed distinct cell clusters reflecting heterogeneity in transcriptional response to treatment, and differences in response was postulated to cause outgrowth of intrinsically resistant melanoma subpopulations.…”
Section: Next-generation Single-cell Rna Sequencing (Sc-rnaseq) In Me...mentioning
confidence: 99%
“…This study proposed therapeutic targets to circumvent treatment resistance. GSE164897 52 Four NRAS-mutant melanoma cell lines treated with MEK and CDK4/6 inhibitors Melanoma cells Differentiated distinct early vs late transcriptional profiles in response to drug treatment. This study identified the ATP-gated ion channel P2RX7 as a potential target in delaying acquired resistance to CDK4/6 inhibitors.…”
Section: Next-generation Single-cell Rna Sequencing (Sc-rnaseq) In Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have employed single-cell RNA sequencing (scRNA-seq) to identify subpopulations present within melanoma tumours based on gene expression signatures ( Figure 1 C). Despite the use of different approaches to identify cell states, there are similarities in the findings [ 54 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ]. Thus far, up to seven distinct transcriptional melanoma cell states have been identified, although a consensus regarding the naming of these populations is yet to be reached ( Table 2 ).…”
Section: Discoveries From Single-cell Sequencingmentioning
confidence: 99%